Multiculturalism And Value Education In History Learning (Case Study At Sman 1 Kartasura) - Hanpalam, Teodorikus (Universitas Sebelas Maret, 2020)
This research was conducted at SMA Negeri 1 Kartasura. This study aims to: (1). To find out the role of multiculturalism in value education. (2). To find out historical learning based on multiculturalism values. The research method used in this research is descriptive analysis with a single case study research strategy. Sources of data in this study are informants, places/locations, and events, as well as documents and archives. The sampling technique used in this research is purposive sampling and time sampling. The technique of data validity is done by triangulation of data/sources and triangulation of methods. The data analysis technique used in this research is an interactive analysis. Benefits of Research: (1). As an illustration regarding the role of multiculturalism in value education. (2). To understand more deeply about historical learning based on multiculturalism values.